2016
DOI: 10.1016/j.respol.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

CO2-reducing innovations and outsourcing: Evidence from photovoltaics and green construction in North-East Italy

Abstract: The paper investigates whether innovations entailing a perceived reduction of CO2 emissions are related to outsourcing. Some research hypotheses are put forward and tested on a sample of firms in two key 'green-industries', sustainable buildings and photovoltaics, in a regional context (North-East Italy) for which detailed survey-based information could be collected. An impact on CO2 reducing innovations is found for the externalisation of tangible activities only, as opposed to intangibles, whose outsourcing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 61 publications
(46 reference statements)
2
13
0
Order By: Relevance
“…In general, it is observed that there is a different effect depending on the autonomous community in which the firm is located. These results corroborate previous literature on the existence of regional differences in terms of eco‐innovation (Cainelli et al, ; Leoncini et al, ), showing therefore the need to complement the studies that analyse both the effect of the stakeholder and regulations, with the inclusion of regional variables to understand the drivers of eco‐innovation in the firm.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In general, it is observed that there is a different effect depending on the autonomous community in which the firm is located. These results corroborate previous literature on the existence of regional differences in terms of eco‐innovation (Cainelli et al, ; Leoncini et al, ), showing therefore the need to complement the studies that analyse both the effect of the stakeholder and regulations, with the inclusion of regional variables to understand the drivers of eco‐innovation in the firm.…”
Section: Resultssupporting
confidence: 89%
“…Thus, the density of firms, regional demand, and regional proximity, among others, have been factors that have had a positive impact on innovation in firms (Cooke et al, ; Fritsch, ; Oerlemans & Meeus, ). However, geographic and regional factors, which have been widely investigated in the literature of innovation, have been poorly studied in the literature of eco‐innovation (Antonioli, Borghesi, & Mazzanti, ; Cainelli et al, ; Ghisetti & Quatraro, , ; Leoncini, Montresor, & Rentocchini, ; Zubeltzu‐Jaka et al, ). Although eco‐innovation has important singularities with regard to innovation, for example, eco‐innovation might generate a “win–win” set‐up characterized by the compatibility of economic development and sustainable economy, or the effect double externality, or regulatory push/pull effect (e.g., Costantini et al, ; Doran & Ryan, ), and so on, the regional perspective may be useful for creating a better understanding of the eco‐innovations and serve as a basis for the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Still, increasing evidence is amounting about the relevance of geography and spatial elements for green technologies and eco-innovations (e.g. Turner, 2006;Munday and Roberts, 2006;Cainelli et al, 2012;Ghisetti and Quatraro, 2013;Horbach, 2014;Antonioli et al, 2016;Leoncini et al, 2016).…”
Section: Background Literaturementioning
confidence: 99%
“…We are especially interested in the relative role of domestic and foreign firms, and in the effect of place-based regional development policy (the special economic zones policy that facilitated FDI and new business creation during the transition period) and the effects of technology policy on air pollution emissions. Recent literature on this topic has brought to the fore the interplay between institutional and technological changes that are often spelled out at the regional level (Costantini and Mazzanti, 2012;Leoncini et al, 2016). This calls for a comprehensive assessment of the set of policy instruments that shape relevant economic incentives (Flanagan et al, 2011;Bachtler and Turok, 2013), including different aspects of the policy mix for sustainable transitions (Rogge and Reichardt, 2016;Edmondson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%